Une diplomatie sur le temps long - Zoe Plaza Leroux (Medievalista)
The study of matrimonial negotiations previously characterised by the perception of the Crown Princes as mere objects of negotiation in diplomatic affairs, reveals a different perspective in the light of the Anglo-Aragonese marriage project of 1268-1285. Peter of Aragon and his son Alfonso were indeed central players in these negotiations. The article explores the active role that certain royal heirs play in diplomatic affairs. This new role accompanied the establishment of the principle of succession in the Crown of Aragon in the 13th century, which transformed the figure of the crown prince into an embodiment of the future of the dynasty. His involvement in diplomatic affairs thus enables him to prepare for his future role as king, but also to consider diplomatic actions in the long term of the dynasty, beyond the mere duration of a reign.